FACEBOOK IRELAND LTD v VOXER IP LLC. Issue 1 (11th March 2023) - ,
Abstract: H1 Patents — European patents — Telecommunications — Live broadcast features —Infringement — Validity—Skilled person — Common general knowledge — Proposed amendments — Construction — Clarity — Added matter — Infringement on normal construction — Equivalence — Formstein defences — Obviousness — Insufficiency — Enablement